An entomoepidemiological investigation of Chagas disease in the state of Ceará, Northeast Region of Brazil - Carolina Fausto de Souza Coutinho; Reinaldo Souza-Santos; Natalia Faria Daflon Teixeira; Ingebourg Georg; Taís Ferreira Gomes; Marcio Neves Boia; Neilane Bertoni dos Reis; Alexander de Oliveira Maia; Marli Maria Lima (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The seroprevalence of Chagas disease in humans and the presence of triatomines were investigated in a rural locality in the State of Ceará, Brazil, an historically endemic region. Approximately 80% of the surveyed residents agreed to undergo serological tests. Intradomestic and peridomestic environments were searched for triatomines in both the dry and rainy seasons. The prevalence rate of Chagas disease was 1.2% and the majority of individuals confirmed with the disease over 50 years of age. A total of 761 specimens of triatomines were captured, most of which were from colonies composed of nymphs and adult bugs, and the majority of specimens were obtained in the dry season. Triatoma brasiliensis was the predominant species. Analysis using light microscopy revealed that 28.6% of the insects were Trypanosoma cruzi positive. Results suggest that peridomestic man-made structures, such as animal shelters, improper storage of timber and uninhabited dwellings contribute to the high rate of triatomine infestation in the area.